Mobile housing design: overview of current trends - Khymytsia, Olha (Видавництво Львівської політехніки, 2017)
The relevance of using mobile housing is substantiated, its classification is based on an own version of a mobile home (transformer type).
Keywords: design; designing mobile housing; mobile houses of container type; modularity of mobile housing; transformation; adaptation; environmental friendliness; using renewable energy sources; energy saving houses